Improved Bio-Synthesis of 2,5-bis(hydroxymethyl)furan by Burkholderia contaminans NJPI-15 With Co-substrate - Chang, Siyuan; He, Xuejun; Li, Bingfeng; Pan, Xin (Frontiers in Chemistry, 2021)
Upgrading of biomass derived 5-hydroxymethylfurfural (HMF) has attracted considerable interest recently. A new highly HMF-tolerant strain of Burkholderia contaminans NJPI-15 was isolated in this study, and the biocatalytic reduction of HMF into 2,5-bis(hydroxymethyl)furan (BHMF) using whole cells was reported. Co-substrate was applied to improve the BHMF yield and selectivity of this strain as well as HMF-tolerant level. The catalytic capacity of the cells can be substantially improved by Mn2+ ion. The strain exhibited good catalytic performance at a pH range of 6.0–9.0 and a temperature range of 25°C–35°C. In addition, 100 mM HMF could be reduced to BHMF by the B. contaminans NJPI-15 resting cells in presence of 70 mM glutamine and 30 mM sucrose, with a yield of 95%. In the fed-batch strategy, 656 mM BHMF was obtained within 48 h, giving a yield of 93.7%. The reported utilization of HMF to produce BHMF is a promising industrially sound biocatalytic process.